ECONOMIC ESSENCE AND RISK MANAGEMENT - Шило, Жанна (SWorldJournal, 2025)
The article studies the economic nature and management of risks. Problems and shortcomings in the classification of risks and clarification of their differences from the category of uncertainty are identified. A methodology for analyzing the main risk ma